Immediate reduction of serum citrulline but no change of steroid profile after initiation of metformin in individuals with type 2 diabetes. Issue 174 (November 2017) - Breier, Michaela; Wahl, Simone; Prehn, Cornelia; Ferrari, Uta; Sacco, Vanessa; Weise, Michaela; Grallert, Harald; Adamski, Jerzy; Lechner, Andreas
Highlights: One dose of metformin already lowers serum citrulline in individuals with previously untreated type 2 diabetes. This effect is sustained for at least 4–6 weeks of metformin treatment. The steroid hormone profile is unchanged by metformin intake in subjects from the general population with type 2 diabetes. Our findings are unlike previous findings in women with Polycystic Ovary Syndrome (PCOS). Abstract: Metformin is the most important first-line treatment for type 2 diabetes mellitus (T2DM) but its exact mode of action remains unknown. In this study, we used targeted metabolomics to gain new insights into the metabolic effects of metformin in humans with T2DM. We also examined changes in the serum steroid hormone profile. We quantified 167 serum metabolites and 19 steroid hormones using liquid chromatography-tandem mass spectrometry at three time points in individuals with previously untreated T2DM: before the start of metformin therapy (time point A), after the first dose (B) and after short-term therapy for 4–6 weeks (C). For metabolite analysis, we split the study cohort into a discovery and a replication study of 88 and 45 subjects, respectively. The statistical analysis was done using linear mixed-effects models. Among the metabolites quantified, citrulline showed the most pronounced changes. Compared to its baseline serum concentration, citrulline was reduced by 17% after the first dose of metformin (p = 1.34E-07) and by 24% after short-term therapy (p = 2.84E-08) in the discovery study. These results were confirmed in the replication study. The only other metabolite significantly changed after correction for multiple testing was PC ae C36:4 between baseline and 4–6 weeks. The serum steroid hormone profile showed no significant changes after metformin intake. In summary, we observed an immediate and sustained reduction of serum citrulline by metformin in humans. This may be relevant for some of the wanted or unwanted effects of the drug.